Cardiac Involvement in Myotonic Dystrophy Type 2 Patients With Preserved Ejection Fraction: Detection by Cardiovascular Magnetic Resonance. (July 2016) - Schmacht, Luisa; Traber, Julius; Grieben, Ulrike; Utz, Wolfgang; Dieringer, Matthias A.; Kellman, Peter; Blaszczyk, Edyta; von Knobelsdorff-Brenkenhoff, Florian; Spuler, Simone; Schulz-Menger, Jeanette
Abstract : Background—: Myotonic dystrophy type 2 (DM2) is a genetic disorder characterized by skeletal muscle symptoms, metabolic changes, and cardiac involvement. Histopathologic alterations of the skeletal muscle include fibrosis and fatty infiltration. The aim of this study was to investigate whether subclinical cardiac involvement in DM2 is already detectable in preserved left ventricular function by cardiovascular magnetic resonance. Methods and Results—: Twenty-seven patients (mean age, 54±10 years; 20 females) with a genetically confirmed diagnosis of DM2 were compared with 17 healthy age- and sex-matched controls using a 1.5 T magnetic resonance imaging. For myocardial tissue differentiation, T1 and T2 mapping, fat/water-separated imaging, focal fibrosis imaging (late gadolinium enhancement [LGE]), and 1 H magnetic resonance spectroscopy were performed. Extracellular volume fraction was calculated. Conduction abnormalities were diagnosed based on Groh criteria. LGE located subepicardial basal inferolateral was detectable in 22% of the patients. Extracellular volume was increased in this region and in the adjacent medial inferolateral segment ( P =0.03 compared with healthy controls). In 21% of patients with DM2, fat deposits were detectable (all women). The control group showed no abnormalities. Myocardial triglycerides were not different in LGE-positive and LGE-negative subjects ( P =0.47). Six patients had indicators for conduction disease (60% of LGE-positive patients and 12.5% of LGE-negative patients). Conclusions—: In DM2, subclinical myocardial injury was already detectable in preserved left ventricular ejection fraction. Extracellular volume was also increased in regions with no focal fibrosis. Myocardial fibrosis was related to conduction abnormalities.